2007
DOI: 10.1371/journal.pgen.0030058
|View full text |Cite
|
Sign up to set email alerts
|

Novel Crohn Disease Locus Identified by Genome-Wide Association Maps to a Gene Desert on 5p13.1 and Modulates Expression of PTGER4

Abstract: To identify novel susceptibility loci for Crohn disease (CD), we undertook a genome-wide association study with more than 300,000 SNPs characterized in 547 patients and 928 controls. We found three chromosome regions that provided evidence of disease association with p-values between 10−6 and 10−9. Two of these (IL23R on Chromosome 1 and CARD15 on Chromosome 16) correspond to genes previously reported to be associated with CD. In addition, a 250-kb region of Chromosome 5p13.1 was found to contain multiple mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
369
0
5

Year Published

2008
2008
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 514 publications
(392 citation statements)
references
References 21 publications
18
369
0
5
Order By: Relevance
“…Interestingly, in a very recent study McCarroll et al 56 have shown that the causal variant responsible for IRGM Figure 1 Pooled data for the ATG16L1 rs2241880 susceptibility allele frequency (SAF). (a) Pooled data of Australian, 39 Belgian, 16 British, 14,21,23,25 Canadian, 31 Dutch, 28 German, 14,29,30 Italian, 27,33 Hungarian, 34 Japanese, 22 New Zealander, 26 North American 15,24 and Spanish cohorts for Crohn's disease (CD). (b) Pooled data of Australian, 39 British, 21,23,37 Canadian, 31 Dutch, 28 German, 14,29,30 Italian, 33 Hungarian, 34 New Zealander, 26,39 North American 15 and Spanish cohorts for ulcerative colitis (UC).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, in a very recent study McCarroll et al 56 have shown that the causal variant responsible for IRGM Figure 1 Pooled data for the ATG16L1 rs2241880 susceptibility allele frequency (SAF). (a) Pooled data of Australian, 39 Belgian, 16 British, 14,21,23,25 Canadian, 31 Dutch, 28 German, 14,29,30 Italian, 27,33 Hungarian, 34 Japanese, 22 New Zealander, 26 North American 15,24 and Spanish cohorts for Crohn's disease (CD). (b) Pooled data of Australian, 39 British, 21,23,37 Canadian, 31 Dutch, 28 German, 14,29,30 Italian, 33 Hungarian, 34 New Zealander, 26,39 North American 15 and Spanish cohorts for ulcerative colitis (UC).…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][21][22][23][24][25][26][27][28][29][30][31][32][33][34]38,39 Funnel plots and Egger tests were performed to analyse the publication bias of the meta-analysis. No statistically significant values were observed in CD studies (P ¼ 0.6) or UC studies (P ¼ 0.4), with symmetric funnel plots for both studies (Supplementary Figure 1).…”
Section: Association Of Atg16l1 and Irgm With Ibd Rj Palomino-moralesmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4] The incidence of IBD is relatively higher in Caucasian than in Asian populations; however, the incidence in Asia is increasing. 5,6 Of the two types of IBD, the genetic contribution to disease risk has been documented more extensively and clearly for CD [7][8][9][10][11][12][13][14][15][16][17] than for UC. [18][19][20][21] So far, linkage and genome-wide association studies have identified more than 30 CD-susceptibility loci in Caucasian populations.…”
Section: Introductionmentioning
confidence: 99%